Non-infectious uveitis burden on quality of life and work impairment assessed through different psychometric questionnaires. Issue 4 (July 2022) - Cimino, Luca; Neri, Piergiorgio; Miserocchi, Elisabetta; Paroli, Maria Pia; Vannozzi, Lorenzo; Mastropasqua, Leonardo; Gagliano, Caterina; Vadalà, Maria; Figus, Michele; Florio, Francesca Romana; Iaccheri, Barbara; Mora, Paolo; et al.
Background: The purpose of this study was to evaluate the association between a novel psychometric 12-item questionnaire (U-qest) and other validated questionnaires to assess quality of life and work impairment in patients with non-infectious uveitis. Methods: Data were collected at baseline and 3 months postbaseline using U-qest and two other validated questionnaires: The National Eye Institute 25-Item Visual Function Questionnaire (VFQ-25) and the 12-Item Short-Form Health Survey (SF-12). Results: A total of 136 patients (52.2% female) aged 47.9 ± 14.8 years (mean ± SD) were enrolled in 14 uveitis referral centres. U-qest correlated moderately with VFQ-25 and SF-12 at baseline and at 3 months. Both U-qest and VFQ-25 scores improved as disease improved; however, U-qest also detected improvement in patients for whom VFQ-25 scores did not improve. Disease activity was shown to significantly affect activity impairment. Patients and physicians expressed positive perceptions regarding the use and benefit of this instrument. U-qest showed very good reliability in terms of internal consistency (Cronbach's alpha = 0.91). Conclusions: U-qest can be considered a useful tool to assess the burden of uveitis on quality of life.